Comparison of Prevalence of the Metabolic Syndrome by Using Different Defining Criteria - Khan, MMR; Haque, Md Zahirul; Rahman, MK; Chowdhury, MMH; Haque, Md Azizul; Rashid, MH; Alim, MA; Mahmood, I; Islam, QT; Chowdhury, MAJ (TAJ: Journal of Teachers Association, 2010)
This cross sectional study was done to see the prevalence of the metabolic syndrome and its components among patients attending in the medicine out patient department of BSMMU by using different defining criteria. The metabolic syndrome according to the modified NCEP ATP III criteria was 27.2% (female 32.41% > male 21.7%). However, according to original NCEP ATP III criteria, proportion of the metabolic syndrome was 22.5% (female 30.6% > male 13.7%). But the metabolic syndrome defined by the modified WHO criteria was 9.0% (male 10.6% > female 7.5%). Comparative analysis of the metabolic syndrome indicated that the proportion of the metabolic syndrome differs in different criteria. In modified WHO criteria the metabolic syndrome was less then NCEP ATP III (modified and original) criteria and there was male preponderance. The proportion of the metabolic syndrome defined by modified and original ATP III criteria is more or less similar. TAJ 2010; 23(1): 10-14